A Differential Approach to Choosing Extracorporeal Detoxification Methods for Abdominal Sepsis - L. Ye Shukevich; Yu. A. Churlyaev; Ye. V. Grigoryev; D. L. Shukevich; K. N. Kondyukov; A. S. Razumov (Общая реаниматология, 2005)
A differential approach to choosing the methods of extracorporeal detoxification in the complex treatment of abdominal sepsis in the context of endogenous intoxication in order to enhance the efficiency of medical measures was pathogeneti-cally substantiated. In 51 patients diagnosed as having abdominal sepsis, the latter was characterized as the endogenous intoxication syndrome in relation to the accumulation of low and medium molecular-weight substances (plasma and red blood cells) in the body and their physiological elimination with urine. An original formula was used to calculate the integral marker – the endogenous intoxication index correlating with the routine severity rating scales APACHE II and SOFA and reflecting the severity of endotoxicosis. According to the values of the endogenous intoxication index and to the sum of scores by the APACHE II and SOFA scales, the patients were divided into 3 groups of the clinicopathogenetic types of endogenous intoxication. According to the type of endogenous intoxication, the authors proposed a differential approach to choosing the modes of efferent therapy for abdominal sepsis: high-volume plasmapheresis in the subcompensated type and prolonged venovenous hemofiltration, which improved the results of treatment and reduced mortality rates.